Safety and immunogenicity of 2010–2011 A/H1N1pdm09-containing trivalent inactivated influenza vaccine in adults previously given AS03-adjuvanted H1N1 2009 pandemic vaccine: Results of a randomized trial - Scheifele, David W. (Landes Bioscience, 2013)
Many Canadians received a novel AS03-adjuvanted vaccine during the 2009 influenza A/H1N1 pandemic. Longer term implications of adjuvant use were unclear: would anti-H1N1 immune responses persist at high levels and, if so, could that result in increased or unusual adverse effects upon re-exposure to H1N1pdm09 antigen in the trivalent influenza vaccine (TIV) for 2010–11? To answer these questions, adults given AS03-adjuvanted H1N1pdm09 vaccine (Arepanrix(®), GSK Canada) 9–10 mo earlier were enrolled in an evaluator-blinded, crossover trial to receive 2010–2011 non-adjuvanted TIV (Fluviral(®), GSK Canada) and placebo 10 d apart, in random order. Adverse effects were monitored for 7 d after each injection. Vaccine-attributable adverse event (VAAE) rates were calculated by subtracting rates after placebo from those after vaccine. Blood was obtained pre-vaccination and 21–30 d afterward to measure hemagglutination inhibiting antibody titers. In total, 326 participants were enrolled and 321 completed the study. VAAE rates were low except for myalgia (18.6%) and injection site pain (63.2%). At baseline, H1N1pdm09 titers ≥ 40 were present in 176/325 subjects (54.2%, 95% confidence interval 48.6, 59.7), with a geometric mean titer (GMT) of 37.4 (95% CI 32.8, 42.6). Post-immunization, 96.0% (95% CI 92.3, 97.8) had H1N1pdm09 titers ≥ 40, with GMT of 167.4 (95% CI 148.7, 188.5). Responses to both influenza A strains in TIV were similar, implying no lasting effect of adjuvant exposure. In summary, titers ≥ 40 persisted in only half the participants 9–10 mo after adjuvanted pandemic vaccine but were restored in nearly all after TIV vaccination, with minimal increase in adverse effects.